The role of light and vision in farmed ungulates and implications for their welfare - Stuhlträger, Julia; von Borell, Eberhard; Langbein, Jan; Nawroth, Christian; Rørvang, Maria Vilain; Raoult, Camille M. C. (Frontiers in Animal Science, 2025)
Understanding the impact of light on, and how it is perceived by, farm animals is crucial for the design of appropriate, high-welfare housing and management conditions. By considering the animal’s visual needs and adaptive capabilities, future housing and management can allow them to better express their natural behavior. In the past, animal environments have been designed primarily to optimize production output and adjusted to human needs. This emphasis has changed toward a more animal-based focus. However, especially in farmed ungulates, there is still limited knowledge about the impact of light parameters on their physiology, performance, and behavior. This poses the risk of not appropriately assessing the importance of these abilities when the animals interact with their physical environment. Here, we provide an overview of the current state of research on the impact of light parameters on farmed ungulates and their preferences for light settings in the most common farmed ungulate species: pigs, sheep, goats, cattle and horses. We focus on three specific light parameters: photoperiod, illumination, and color. Secondly, we identify gaps of knowledge and emphasize their implications for animal welfare and potential improvement of current animal husbandry environments. There was considerable variation in the number of studies by species and light parameters. A large focus of studies looked at illumination in pigs and color perception in horses. Research on cattle, sheep and goats, seems to be underrepresented in the literature. From a human perspective, we tend to overestimate the importance of color perception and preference, whereas contrast discrimination in combination with illumination intensity and quality seems to be more relevant for ungulate orientation and interaction with their environment. Aside from the importance of other senses and their interaction with vision, we conclude that illumination and photoperiodicity seem to be most relevant for securing the welfare of farm ungulates. These aspects should therefore be given more consideration in indoor housing improvements. Future research emphasis should be given to preference testing studies, as they provide insights into the animals’ motivation for specific light conditions that may further improve their welfare, but also health and performance.